Update on toll-like receptor-directed therapies for human disease. (12th October 2007) - Tse, Kevin; Horner, Anthony A
Abstract : Innate responses to microbes are mediated in large part by toll-like receptors (TLRs), which recognise a diverse range of molecules produced by viruses, bacteria and fungi. Great effort has been directed towards translating this knowledge into the development of new therapies for a wide spectrum of diseases, including infectious, malignant, autoimmune and allergic diseases. This review will provide a brief update on completed, ongoing and planned clinical trials of TLR ligand-based therapies for the treatment of diseases in humans.